EFFECT of COHERENT STRUCTURES on ENERGETIC PARTICLE INTENSITY in the SOLAR WIND at 1 AU - Jeffrey A. Tessein (2018)
© 2015. The American Astronomical Society. All rights reserved.. We present results from an analysis of Advanced Composition Explorer (ACE) observations of energetic particles in the 0.047-4.78 MeV range associated with shocks and discontinuities in the solar wind. Previous work found a strong correlation between coherent structures and energetic particles measured by ACE/EPAM. Coherent structures are identified using the Partial Variance of Increments (PVI) method, which is essentially a normalized vector increment. The correlation was based on a superposed epoch analysis using over 12 years of data. Here, we examine many individual high-PVI events to better understand this association emphasizing intervals selected from data with shock neighborhoods removed. We find that in many cases the local maximum in PVI is in a region of rising or falling energetic particle intensity, which suggests that magnetic discontinuities may act as barriers inhibiting the motion of energetic particles across them.